2022
DOI: 10.3892/mco.2022.2546
|View full text |Cite
|
Sign up to set email alerts
|

Application of J‑Plasma in the excision of diaphragmatic lesions as part of complete cytoreduction in patients with advanced ovarian cancer

Abstract: For the resection of diaphragmatic disease in patients with advanced ovarian cancer (OC), a plethora of ablative methods have been utilized. The present study aimed to present preliminary data on the use of J-Plasma in OC with diaphragmatic involvement via a retrospective review of patients who had diaphragmatic stripping with of J-Plasma ® from January 2016 to September 2020. A total of 12 patients (median age, 65 years) were analyzed. Median operative time was 240 min while median estimated blood loss was 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Recently, Theodoulidis et al in their retrospective analysis of the surgical treatment of patients with advanced ovarian cancer concluded that J-Plasma could be safely used in diaphragmatic resection with no J-Plasma-related complications and no defect in diaphragmatic integrity (17). These results are confirmed by our study, despite the smaller number of diaphragmatic resections on our cohort.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Theodoulidis et al in their retrospective analysis of the surgical treatment of patients with advanced ovarian cancer concluded that J-Plasma could be safely used in diaphragmatic resection with no J-Plasma-related complications and no defect in diaphragmatic integrity (17). These results are confirmed by our study, despite the smaller number of diaphragmatic resections on our cohort.…”
Section: Discussionsupporting
confidence: 87%